Role of Quetiapine in the Prevention of ICU Delirium in Elderly Patients at a High Risk - Kamel Walid Y.; Kamel Heba Y.; Elsherif Ibrahim M. (The Journal of Critical Care Medicine)
The aim of the present study was to denote the effectiveness of Quetiapine as additive to preventive bundle of delirium in elderly patients with multiple risks for delirium.